Peningkatan Kemampuan Memerankan Tokoh Drama Dengan Menggunakan Teknik Bermain Drama Rendra - Fiki Rona Padang; Mutia Febriyana; Roslinansyah Sitorus (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In learning drama materials and drama performances in class XI AKL1, there are several problems faced by students, such as difficulties in playing characters in dramas, and a lack of active involvement in the learning process. To overcome this problem, it is necessary to use more creative learning techniques and media. One of the solutions adopted in this study is the use of rendra drama techniques and technology in learning. The use of rendra drama techniques in learning has the potential to increase students' interest and learning motivation in playing drama characters. The purpose of this study was to improve students' speaking skills in playing drama characters by paying attention to the building elements of a drama performance. This study has two objectives, namely (1) to describe Rendra's drama playing techniques and (2) to apply the use of Rendra's drama playing techniques to drama learning for class XI AKL-1 for the 2022/2023 academic year. The method used is a qualitative description. Descriptive based on Class action research (CAR). The data validity technique used in this research is data triangulation (source) and method triangulation. The data analysis technique used is qualitative data analysis used to analyze data that occurs in the teaching and learning process. Based on the research results, two conclusions can be drawn. Action research class (CAR) was conducted in two cycles, namely cycle 1 and cycle 2. Each cycle experienced an increase in student learning outcomes. At the pre-cycle stage, the percentage of students who achieved learning mastery was 57.43%. Then, in cycle 1, this figure increased to 66.28%. After going through cycle 2, the percentage of students who achieved learning mastery increased again to 89.14%. Thus, Rendra's drama playing technique can be chosen as a superior and appropriate learning technique in playing drama which can lead students to have the ability to play drama characters according to various techniques. applied in the learning process.